Simultaneous proton density, T1, T2, and flip‐angle mapping of the brain at 7 T using multiparametric 3D SSFP imaging and parallel‐transmission universal pulses. Issue 6 (3rd July 2020) - Leroi, Lisa; Gras, Vincent; Boulant, Nicolas; Ripart, Mathilde; Poirion, Emilie; Santin, Mathieu D.; Valabregue, Romain; Mauconduit, Franck; Hertz‐Pannier, Lucie; Le Bihan, Denis; de Rochefort, Ludovic; Vignaud, Alexandre
Abstract : Purpose: Performing simultaneous quantitative MRI at ultrahigh field is challenging, as B0 and B 1 + heterogeneities as well as specific absorption rate increase. Too large deviations of flip angle from the target can induce biases and impair SNR in the quantification process. In this work, we use calibration‐free parallel transmission, a dedicated pulse‐sequence parameter optimization and signal fitting to recover 3D proton density, flip angle, T1, and T2 maps over the whole brain, in a clinically suitable time. Methods: Eleven optimized contrasts were acquired with an unbalanced SSFP sequence by varying flip‐angle amplitude and RF phase‐cycling increment, at a 1.0 × 1.0 × 3.0 mm 3 resolution. Acquisition time was 16 minutes 36 seconds for the whole brain. Parallel transmission and universal pulses were used to mitigate B 1 + heterogeneity, to improve the results' reliability over 6 healthy volunteers (3 females/3 males, age 22.6 ± 2.7 years old). Quantification of the physical parameters was performed by fitting the acquired contrasts to the simulated ones using the Bloch‐Torrey equations with a realistic diffusion coefficient. Results: Whole‐brain 3D maps of effective flip angle, proton density, and relaxation times were estimated. Parallel transmission improved the robustness of the results at 7 T. Results were in accordance with literature and with measurements from standard methods. Conclusion: These preliminary results show robust proton density, flip angle, T1, and T2 map retrieval. Other parameters, such as ADC, could be assessed. With further optimization in the acquisition, scan time could be reduced and spatial resolution increased to bring this multiparametric quantification method to clinical research routine at 7 T.